Life-threatening vitamin D intoxication due to intake of ultra-high doses in multiple sclerosis: A note of caution. (August 2019) - Feige, Julia; Salmhofer, Hermann; Hecker, Constantin; Kunz, Alexander Baden; Franzen, Michael; Moré, Elena; Sellner, Johann
Knowledge about complications of chronic ultra-high dose vitamin D supplementation is limited. We report a patient with primary progressive multiple sclerosis (MS) who presented with generalized weakness caused by hypercalcemia after uncontrolled intake of more than 50, 000 IU of cholecalciferol per day over several months. Various treatment strategies were required to achieve normocalcemia. However, renal function improved only partly and further progression of MS was observed. We conclude that patients need to be informed about the risks of uncontrolled vitamin D intake and neurologists need to be alert of biochemical alterations and symptoms of vitamin D toxicity.